Esporte e valores sociais - Kirst, Flavio Valdir (2009)
There is a consensus on the fact that the sport, as socializing tool, could be a source of social guiding values, whether positive or negative. However, there is a lack of empirical data to support such consensus. The aim of this paper was to investigate if the sport values are, in fact, present in other spheres of sportsman/sportswoman social life, taking as theoretical references the Critical Theory of Sport and the Theory of Brazilian Dilemma. We adopted a semi-structured questionnaire with five attitude scales related to the following categories: 1) discipline, 2) ability of social navigation, 3) fungible principle, 4) meritocracy, 5) principle of performance, 6) reorganization of order. The research locus was the national round of the 15 to 17 years old School Olympics (João Pessoa, PB, 2008). 498 questionnaires was released to athletics, basketball, futsal, judo, handball and volleyball athletes. 261 questionnaires were answered. The Chi-Square was used to test discrepancies according to sex and sport. To better interpret data, in-depth interviews were conducted with 21 respondents. The results confirmed Critical Theory postulates related to the categories ‘discipline’, ‘fungible principle’, ‘meritocracy’ and ‘performance principle’. However, one could observe divergences toward the notions of unconditional respect of the rules and hierarchies, the belief of the victory as a personal merit, and the winning as a ultimate goal. On the other hand, the results confirmed postulates related to the categories of ability of social navigation, meritocracy and the reorganization of order of the Brazilian Dilemma Theory. One could assert an uncertainty between opposed social values. Thus, we can think on complementarities between different social theories rather than an opposition.